Comparison of Early Outcome of Off-pump and Conventional Coronary Artery Bypass Graft Surgery in Patients with Multivessel Coronary Artery Disease and Left Ventricular Dysfunction - Raha, Sanjay Kumar; Hossain, Md Sorower; Biswas, Smriti Kana; Rahaman, Salahuddin; Ahmad, Manzil; Hasan, Md Kamrul (Bangladesh Heart Journal, 2020)
Introduction: Left ventricular dysfunction is an important predictor of in-hospital mortality. Due to the theoretical and practical advantages to avoid the harmful effects of cardiopulmonary bypass (CPB), many cardiac surgeons are using Off-pump Coronary Artery Bypass (OPCAB)as an effective alternative to conventional CABG (CCAB) even in patients with reduced left ventricular (LV)ejection fraction. Objectives: This study performed in the National Institute of Cardiovascular Diseases (NICVD) evaluated the early outcomes of OPCAB in terms of mortality and major post-operative morbidities and compared them with that of CCAB in patients with multivessel coronary artery diseases and reduced left ventricular (LV) function. Methods: Total 120 patients with multivessel coronary artery disease with reduced left ventricular ejection fraction (d”50%)were allocated into two groups: a) 60 patients who underwent OPCAB and b) another 60 patients who underwent conventional CABG between January 2013 and December 2015. Pre-operative, peroperative and early post-operative variables were recorded, compiled and compared. Results: All risk factors and co-morbidities were homogenously distributed between the two groups. Majority of the patients had triple vessel disease. Nearly three-quarter (73.3%) of patients in OPCAB group and 80% in CCAB group received 3 grafts (p=0.470). The mean total operative time (268.5 ± 33.5vs. 296.3 ± 34.8minutes, p < 0.001), intubation times(8.6±0.3 vs. 12.3±0.5 hours, p<0.001), blood losses (377.8378 ± 45 ml vs. 602 ± 60 ml, p < 0.001); requirements for blood and blood products (689.7±21.1 vs. 1199.3±34.5ml, p < 0.0010),intensive care unit stays (31.7±0.9 hours versus 41.6±1.5 hours; p<0.001) and hospital stays (8.2 ± 0.2days vs.10.3 ± 0.3days, p < 0.001)were all significantly lower in the OPCAB group. Conclusion: OPCAB is a safe and effective operative revascularization procedure for patients with multivessel coronary artery disease and left ventricular dysfunction and is associated with reduced morbidity. However, a larger and omized trial with long-term followup may show the real benefits of OPCAB. Bangladesh Heart Journal 2020; 35(1) : 20-27